Direct Mechanocatalysis: Palladium as Milling Media and Catalyst in the Mechanochemical Suzuki Polymerization. Issue 52 (7th November 2019) - Vogt, Christian G.; Grätz, Sven; Lukin, Stipe; Halasz, Ivan; Etter, Martin; Evans, Jack D.; Borchardt, Lars
Abstract: The milling ball is the catalyst. We introduce a palladium‐catalyzed reaction inside a ball mill, which makes catalyst powders, ligands, and solvents obsolete. We present a facile and highly sustainable synthesis concept for palladium‐catalyzed C−C coupling reactions, exemplarily showcased for the Suzuki polymerization of 4‐bromo or 4‐iodophenylboronic acid giving poly( para ‐phenylene). Surprisingly, we observe one of the highest degrees of polymerization (199) reported so far. Abstract : The milling ball is the catalyst : In a mechanochemical Suzuki polymerization of 4‐bromo‐ or 4‐iodophenylboronic acid yielding poly( para ‐phenylene) the classical Pd catalysts could be replaced by solid Pd milling balls, enabling outstanding degrees of polymerization.